PENGARUH GAYA HIDUP TERHADAP POLA KONSUMSI DAN KEBIASAAN MENABUNG MAHASISWA GENERASI Z DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Alya Aurelia; Anggi Alia Ashari Hsb; M Nabil Putra Hendratmo; Yenni Samri Juliati Nasution (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study is based on lifestyle changes made by Gen Z students, who spend more and save less. Lifestyle influenced by trends and the desire to appear on social media are the main factors that influence shopping and financial behavior, including saving. The purpose of this study was to assess the effect of lifestyle on shopping patterns and saving habits of Gen Z students at the State Islamic University of North Sumatra. This study uses a quantitative method using a survey method. Data analysis was carried out using multiple linear regression using SPSS version 30; a purposive sample consisting of 100 Generation Z students. This study found that lifestyle has a significant and positive effect on shopping patterns, but also has a negative effect on saving habits. In other words, the more students' lifestyles, the more likely they are not to save. This finding is important as a basis for teaching students about financial literacy from an early age, so that they can manage their lifestyles in a more balanced way and develop better financial habits.